2013
DOI: 10.1016/j.cognition.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The test of truth: An experimental investigation of the norm of assertion

Abstract: a b s t r a c tAssertion is fundamental to our lives as social and cognitive beings. Philosophers have recently built an impressive case that the norm of assertion is factive. That is, you should make an assertion only if it is true. Thus far the case for a factive norm of assertion been based on observational data. This paper adds experimental evidence in favor of a factive norm from six studies. In these studies, an assertion's truth value dramatically affects whether people think it should be made. Whereas … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 29 publications
7
91
1
Order By: Relevance
“…While outcome valence did have some impact on the causal ratings of the fixed agent, it did not impact the causal superseding effect, that is, the effect of the moral status of the varied agent"s actions on the fixed agent"s causality. This provides strong evidence that causal superseding can be distinguished from excuse validation (Turri, 2013), and therefore goes beyond the predictions of a motivational account. It is particularly striking that the superseding effect emerges even in cases where participants regarded the outcome as positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While outcome valence did have some impact on the causal ratings of the fixed agent, it did not impact the causal superseding effect, that is, the effect of the moral status of the varied agent"s actions on the fixed agent"s causality. This provides strong evidence that causal superseding can be distinguished from excuse validation (Turri, 2013), and therefore goes beyond the predictions of a motivational account. It is particularly striking that the superseding effect emerges even in cases where participants regarded the outcome as positive.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a series of studies have found that people"s judgments are often distorted by "blame validation" (Alicke, 1992;Alicke, Buckingham, Zell, & Davis, 2008; RUNNING HEAD: CAUSAL SUPERSEDING 6 Lagnado & Channon, 2008), a motivational bias to assign causality to people who are blameworthy, with only minimal regard for their actual causal status. Subsequent work has extended this account to include "excuse validation" (Turri, 2013), the motivation to not assign causality to individuals whom we do not feel are blameworthy. For example, if a driver is speeding because of an accelerator malfunction and gets into a lethal accident, we might be disinclined to regard the driver as a cause of the accident because her actions are blameless.…”
Section: )mentioning
confidence: 99%
“…One study directly investigated whether the norm of assertion was, at the very least, "factive" or truth-entailing. A factive norm implies that only true assertions should be made (Turri 2013; see also Rakoczy and Tomasello 2009). This study was motivated by critics' repeated insistence that the norm of assertion cannot be factive, because factive norms are counterintuitive and mischaracterize the practice of assertion.…”
Section: Introductionmentioning
confidence: 98%
“…It's often assumed that the intuition is widely shared that reasonable ignorant assertions are permissible. But empirical investigation casts serious doubt on that assumption; see Turri (2013e).…”
mentioning
confidence: 99%